Solitons in the Gauged Skyrme-Maxwell Model - Livramento, Leandro Roza; Radu, Eugen; Shnir, Yakov (Symmetry, Integrability and Geometry: Methods and Applications, 2023)
We consider soliton solutions of the U(1) gauged Skyrme model with the pion mass term. The domain of existence of gauged Skyrmions is restricted from above by the value of the pion mass. Concentrating on the solutions of topological degree one, we find that coupling to the electromagnetic field breaks the symmetry of the configurations, the Skyrmions carrying both an electric charge and a magnetic flux, with an induced dipole magnetic moment. The Skyrmions also possess an angular momentum, which is quantized in units of the electric charge. The mass of the gauged Skyrmions monotonically decreases with the increase of the gauge coupling.